Phosphorothioate Oligodeoxyribonucleotides Antisense to PAI-1 mRNA Increase Fibrinolysis and Modify Experimental Thrombosis in Rats - Pawlowska, Zofia; Pluskota, Elzbieta; Chabielska, Ewa; Buczko, Wlodzimierz; Okruszek, Andrzej; Stec, Wojciech J.; Cierniewski, Czeslaw S. (Thrombosis and Haemostasis, 1998)
The effect of systemic inhibition of PAI-1 expression in rats by PS-16R, a phosphorothioate analogue of hexadecadeoxyribonucleotide complementary to a signal peptide coding sequence of rat PAI-1 mRNA, on PAI-1 activity in blood plasma and thrombus formation was studied in rat models for experimental thrombosis. In previous in vitro studies, oligonucleotides of PS-16R family have been shown to inhibit efficiently PAI-1 synthesis in endothelial cells by antisense mechanism. When PS-16R was administered intravenously as a single bolus injection (1 to 5 mg per rat), it produced a significant reduction in PAI-1 activity of blood plasma. This effect was both time- and concentration-dependent. Under the same conditions, three groups of rats were treated with control oligodeoxynucleotides such as PS-16R with double mismatches, with scrambled sequence, and an oligodeoxynucleotide with sense sequence (complementary to PS-16R), respectively. Based on these preliminary experiments, a low dose of 1.5 mg per rat was selected to produce approximately 20-30% reduction of PAI-1 activity in blood plasma and the effect of such a decrease in PAI-1 expression was tested on thrombus formation in two rat models for experimentally induced thrombosis. Such a limited decrease in PAI-1 activity produced a significant antithrombotic effect in the arterial thrombosis model. There was a profound delay in the occlusion time in rats treated with PS-16R when compared to control animals (80 ± 3 and 55 ± 3 h, respec tively), although blood plasma activity of PAI-1 in the same groups of rats differed only by 20%. There was also a tendency to reduce both an incidence of venous thrombosis (58.33 and 68.11%, respectively) and thrombus weight (2.1 ± 0.4 and 2.9 ± 0.9 mg, respectively) in the animals treated with PS-16R. However, this effect was not significant. Thus, low dose of PS-16R through inhibition of PAI-1 synthesis in targeted cells in rats reduced PAI-1 activity in blood plasma and protected against arterial thrombus formation in the rat.